2022
DOI: 10.1101/2022.05.24.493086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alcohol reverses the effects ofKCNJ6(GIRK2) noncoding variants on excitability of human glutamatergic neurons

Abstract: Synonymous and noncoding single nucleotide polymorphisms (SNPs) in the KCNJ6 gene, encoding G protein-gated inwardly rectifying potassium (GIRK2) channel subunit 2, have been linked with increased electroencephalographic frontal theta event-related oscillations (ERO) in subjects diagnosed with alcohol use disorder (AUD). To identify molecular and cellular mechanisms while retaining the appropriate genetic background, we generated induced excitatory glutamatergic neurons (iN) from iPSCs derived from four AUD-di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…The role of KCNJ6 in alcohol‐ and other reward‐related behaviors is supported by multiple independent studies. 100 , 101 , 102 , 103 , 104 , 105 Pursuing this gene using iPSC derived neurons and lymphocytes from COGA participants with and without AUD, we recently showed that neurons derived from AUD COGA subjects express lower levels of GIRK2 and that exposure to levels of ethanol consistent with the human phenotype of intoxication reverses these functional effects 100 (see, 5. Functional Genomics).…”
Section: Genome‐wide Association Studies ( Gwas )mentioning
confidence: 99%
“…The role of KCNJ6 in alcohol‐ and other reward‐related behaviors is supported by multiple independent studies. 100 , 101 , 102 , 103 , 104 , 105 Pursuing this gene using iPSC derived neurons and lymphocytes from COGA participants with and without AUD, we recently showed that neurons derived from AUD COGA subjects express lower levels of GIRK2 and that exposure to levels of ethanol consistent with the human phenotype of intoxication reverses these functional effects 100 (see, 5. Functional Genomics).…”
Section: Genome‐wide Association Studies ( Gwas )mentioning
confidence: 99%